A Common Variant at the 3'untranslated Region of the CCL7 Gene (rs17735770) Is Associated With Decreased Susceptibility to Coronary Heart Disease - Medina-Gil, José María; Pérez-García, Ana; Saavedra-Santana, Pedro; Díaz-Carrasco, Asunción; Martínez-Quintana, Efrén; Rodríguez-González, Fayna; Ramírez, Cristina M.; Riaño, Marta; Garay-Sánchez, Paloma; Tugores, Antonio (Frontiers in Cardiovascular Medicine, 2022)
Monocytes participate in the development of atherosclerosis through the action of cytokines and other inflammatory mediators. Among them, CCR2 and its ligands, CCL2 and CCL7 play an important role, so the main objective of this work was to determine whether genetic variants affecting their activity were associated with cardiovascular disease. A cohort of 519 patients that have suffered coronary events was analyzed under a propensity score-matching protocol selecting a homogeneous set of cases and controls, according to age, sex, smoking status, dyslipidemia, arterial hypertension and type 2 diabetes as risk factors. While dyslipidemia and arterial hypertension were more prevalent among patients with angina pectoris, current smoking status and elevated inflammatory markers, including total leukocyte and monocyte counts, were more likely associated with acute coronary events. Propensity score matching analysis, performed to eliminate the influence of these risk factors and highlight genetic modifiers, revealed that a single nucleotide variant, rs17735770 at the 3' untranslated region of the CCL7 gene transcript, was associated with decreased cardiovascular risk in a group represented mostly by men, with an average age of 57, and without significant differences in traditional risk factors. Furthermore, the presence of this variant altered the local mRNA structure encompassing a binding site for miR-23ab, resulting in increased translation of a reporter gene, independently of the exogenous addition of miR-23a. The rs17735770 genetic varint led to increased expression of CCL7, a potential antagonist of CCR2 at inflammatory sites, where it could play a meaningful role during the evolution of atherosclerosis.